The Chemical and Genetic Characteristics of Szechuan Pepper (Zanthoxylum bungeanum and Z. armatum) Cultivars and Their Suitable Habitat - Xiang, Li; Liu, Yue; Xie, Caixiang; Li, Xiwen; Yu, Yadong; Ye, Meng; Chen, Shilin (Frontiers in Plant Science, 2016)
Szechuan peppers, famous for their unique sensation and flavor, are widely used as a food additive and traditional herbal medicine. Zanthoxylum bungeanum and Z. armatum are both commonly recognized as Szechuan peppers, but they have different tastes and effects. The chemical components, genetic characteristics, and suitable habitat of six cultivars were analyzed in this study. The results indicated that Z. armatum contained a larger proportion of volatile oil, whereas Z. bungeanum produced a more non-volatile ether extraction. The average content of volatile oil and non-volatile ether extract of Z. armatum were 11.84% and 11.63%, respectively, and the average content of volatile oil and non-volatile ether extract of Z. bungeanum were 6.46% and 14.23%, respectively. Combined with an internal transcribed spacer 2 (ITS2) sequence characters and chemical PCA results, six cultivars were classified into their own groups, for the two species in particular. The temperature in January and July were the most significant ecological factors influencing the contents of the Z. armatum volatile oil. However, annual precipitation, temperature in January and relevant humidity had a significant positive correlation with the content of non-volatile ether extract in Z. bungeanum. Thus, the most suitable areas for producing Z. bungeanum cultivars ranged from the Hengduan Mountains to the Ta-pa Mountains, and the regions suitable for Z. armatum cultivars were found to be in the Sichuan Basin and Dalou-Wu mountains. The predicted suitable habitat could be used as a preliminary test area for Szechuan pepper cultivar production.